Is Surgery Still an Option in Pulmonary Arteriovenous Malformations Management? - Karim Nehme; Lamisse Karam; Joseph Nakad; Nader Saad; Georges Tabet (Dubai Medical Journal)
Pulmonary arteriovenous malformations (PAVMs) are fistulous connections between pulmonary arteries and veins, associated with hereditary hemorrhagic telangiectasia. It can be associated with a wide range of complications. Contrast-enhanced computed tomography is the best noninvasive diagnosis modality. Treatment is recommended for symptomatic patients or those having a feeding artery diameter superior to 3 mm. We present here the case of a 69-year-old man with a complex PAVM, peripherally localized with a feeding artery diameter bigger than 3 mm intentionally treated via an open middle lobe wedge resection via axillary mini thoracotomy over embolotherapy, showing that it comes with less risk and at a lower cost.